Galangin Resolves Cardiometabolic Disorders through Modulation of AdipoR1, COX-2, and NF-κB Expression in Rats Fed a High-Fat Diet - Patoomporn Prasatthong; Sariya Meephat; Siwayu Rattanakanokchai; Juthamas Khamseekaew; Sarawoot Bunbupha; Parichat Prachaney; Putcharawipa Maneesai; Poungrat Pakdeechote (MDPI AG, 2021)
Galangin is a natural flavonoid. In this study, we evaluated whether galangin could alleviate signs of metabolic syndrome (MS) and cardiac abnormalities in rats receiving a high-fat (HF) diet. Male Sprague-Dawley rats were given an HF diet plus 15% fructose for four months, and they were fed with galangin (25 or 50 mg/kg), metformin (100 mg/kg), or a vehicle for the last four weeks. The MS rats exhibited signs of MS, hypertrophy of adipocytes, impaired liver function, and cardiac dysfunction and remodeling. These abnormalities were alleviated by galangin (p < 0.05). Interleukin-6 and tumor necrosis factor-α concentrations and expression were high in the plasma and cardiac tissue in the MS rats, and these markers were suppressed by galangin (p < 0.05). These treatments also alleviated the low levels of adiponectin and oxidative stress induced by an HF diet in rats. The downregulation of adiponectin receptor 1 (AdipoR1) and cyclooxygenase-2 (COX-2) and the upregulation of nuclear factor kappa B (NF-κB) expression were recovered in the galangin-treated groups. Metformin produced similar effects to galangin. In conclusion, galangin reduced cardiometabolic disorders in MS rats. These effects might be linked to the suppression of inflammation and oxidative stress and the restoration of AdipoR1, COX-2, and NF-κB expression.